The Gulag Archipelago, 1918-1956 . an experiment in literary investigation - [by] Aleksandr I. Solzhenitsyn ; translated from the Russian by Thomas P. Whitney. (Harper & Row)
Translation of Arkhipelag GULag, 1918-1956. Vol. 3 translated by H. Willetts. Includes bibliographical references.